Pengaruh etika kerja dan stres kerja terhadap kinerja dengan komitmen organisasi sebagai variabel intervening - Wahyuni, Endah Tri; Hadiwijaya, Dudung; Susilo, Priyo (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
The research aims to examine the influence of work ethics and work stress on employee performance and examine the mediating role of organizational commitment on the influence of work ethics and work stress on performance. This study uses a quantitative approach. The population in this study were all employees at the Tangerang Regency Fisheries Service, totaling 75 people. Data collection techniques from respondents using online questionnaires. Data analysis methods include instrument testing, classical assumption testing, model feasibility testing, hypothesis testing and path analysis. This research reveals that work ethics has a significant effect on employee commitment, work stress has no significant effect on organizational commitment, work ethics has a significant effect on employee performance, work stress has no significant effect on performance and organizational commitment has a significant effect on performance. Organizational commitment does not play a role as a mediator of work ethics and work stress on employee performance.